Cultivating sustainable capacity to build a thriving entrepreneurial ecosystem in Kenyan universities - Murithi, William; Ebie, Samuel; Pickenell, David; Doneddu, Daniel; Mungai, Edward; Gachambi, Patricia; Kateeti, Morris; Korrir, Phylis (Strathmore University Press, 2025)
Kenyan universities face a dual challenge in their aspirations to be both centres of quality education and sources of innovation and economic development. This policy brief is based on extensive research into the universities’ academic curricula. The study reveals that although some institutions, such as Strathmore University, have established effective and multi-tiered entrepreneurial programmes, many barriers exist. These include limited funding, faculty member training, and a lack of follow-up after students graduate. With an emphasis on curricular integration and continuous review, as well as improved industry-government partnerships and the introduction of specific faculty support mechanisms, universities are better positioned to convert academic research into practical policy and discover a new generation of job creators, thereby complementing national development objectives. In the long run, when most graduating students can create jobs for themselves and others, it could help reduce Kenya's 8.4% youth unemployment rate. Keywords: Kenyan universities, academic curricula, entrepreneurial programmes, job creation
[i] Dr William Murithi, a senior faculty member, researcher, and consultant at Strathmore Business School, specialises in entrepreneurship, strategy, and family business. [ii] Dr Samuel Ebie, Lecturer in Entrepreneurship and Innovation at Swansea University and Deputy Director of the Innovation and Entrepreneurship Research Institute (IERI), has extensive experience in enterprise, small business, and higher education leadership. [iii] Prof. David Pickenell is Professor of Small Business and Enterprise Development Policy at the Swansea University School of Management and the Director of the Innovation and Entrepreneurship Research Institute (IERI). [iv] Dr Daniele Doneddu is a Senior Lecturer at Swansea University’s School of Management. He has a multidisciplinary background spanning engineering, medical technology, innovation, economic development and IP. [v] Dr Edward Mungai, Deputy Vice-Chancellor for Partnerships and Development at Strathmore University, focuses on youth employment, family well-being, and ethical business practices. [vi] Dr Patricia Gachambi, Director of Undergraduate Programmes at Strathmore Business School, specialises in strategic management and competitive advantage. [vii] Morris Mbaluka, a statistician and policy researcher at KIPPRA, works on applied statistics, entrepreneurship, and innovation ecosystems to support sustainable development. [viii] Phylis Korir is a quantitative researcher and Monitoring and Evaluation specialist at iBiz Africa.